2011
DOI: 10.1152/ajpgi.00251.2010
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β and ADAM17 are central regulators of β-defensin expression in Candida esophagitis

Abstract: Candida albicans resides on epithelial surfaces as part of the physiological microflora. However, under certain conditions, it may cause life-threatening infections, including Candida sepsis. We have recently shown that human β-defensins (hBDs) hBD-2 and hBD-3 are upregulated in Candida esophagitis and that this antifungal host response is distinctly regulated by NF-κB and MAPK/activator protein-1 (AP-1) pathways. Here, we show that C. albicans induces hBD-2 through an autocrine IL-1β loop and that activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
(76 reference statements)
2
17
0
Order By: Relevance
“…Here we showed that blocking of EGFR or inhibition of ADAM17 reduced the level of expression of hBD-3 induced by A. baumannii but had little effect on the level of hBD-2 induction. This observation is in line with the findings with Candida infections (33,40). Together, these results suggest that there might be a common theme in innate molecules induced in the course of microbial infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here we showed that blocking of EGFR or inhibition of ADAM17 reduced the level of expression of hBD-3 induced by A. baumannii but had little effect on the level of hBD-2 induction. This observation is in line with the findings with Candida infections (33,40). Together, these results suggest that there might be a common theme in innate molecules induced in the course of microbial infection.…”
Section: Discussionsupporting
confidence: 91%
“…Several reports have indicated that EGFR activation plays a critical role in hBD-3 induction in Candida esophagitis (33,40) and Helicobacter pylori infection (41). Here we showed that blocking of EGFR or inhibition of ADAM17 reduced the level of expression of hBD-3 induced by A. baumannii but had little effect on the level of hBD-2 induction.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we demonstrated that mRNA abundance of IL-1b paralleled the changes in the up-regulated AMPs in the inflamed appendices. IL-1b is known to be crucial for induction of hBD-2 abundance, 14 especially in the course of fungal infections. 38 Besides IL-1b, TNF-a and IL-6, IL-8 and IL-10 were induced.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Defensins are envisaged to play significant roles in intestinal microbial homeostasis and in the primary defense against enteral and systemic infections. [11][12][13][14][15] In this study, we investigated the mRNA expression of AMPs, their potential upstream regulators and changes in bacterial diversity in acute appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory signaling of epithelial cells is activated further by cohabiting neutrophils, which induce upregulation of TLR4 (39), which in normal human skin may already be upregulated by contact with Gram-positive bacteria (40). TLR4 not only binds O-mannans in the C. albicans cell wall but also the defensin hBD2, which generates an autostimulatory feedback loop in epithelial cells; in addition, an autocrine IL-1␤ loop augments transcriptional responses (41). Zones of fungal infection become increasingly inflamed due to the chemoattractive activities of AMPs that recruit more lymphocytes (reviewed in reference 42).…”
Section: Regulated Amp Activity Against C Albicansmentioning
confidence: 99%